Unpublished Ur III texts: Ageština field - Dhahir, Ishtar (Al-Adab Journal, 2024)
this article presents four cuneiform tablets from the confiscated collection in the Iraq Museum in Baghdad. The texts likely originate from the Umma provenance and are dated to the reigne of Amarsuen (AS9) and šusuen (šS2) of the Ur III dynasty. The tablets contain information about the field Ageština, which is also mentioned in Ur III texts. We trace the location of a- ša3-a-ge štin-na,the area of the Ageština, and agricultural processes through additional texts available in the BDTNS database, complementing the information found in our unpublished texts.